'Where do you want to go today?' An analysis of family group decisions to visit museums - Wu, K.; Holmes, Kirsten; Tribe, J. (Routledge, 2010)
Families with children are important arts audiences. Yet, few studies have examined the pre-purchase behaviour of this market segment. In contrast to previous research, this paper employs an interpretative approach to study the interactive dynamics of family groups within a single decision context. The data were obtained from the participants' recollection of a freshly made decision – the decision to visit a museum. Based on group interviews with 37 families with children, this paper demonstrates the joint decisions made by the adults and children together, and identifies four decision patterns. The findings contribute new insights into the active roles that children play in museum consumption, including making purchase requests and suggestions, and acting as the decision makers. This paper also clarifies the role of each child in the decision-making process. A model for joint decision making is proposed for further testing and development in future research.